2018
DOI: 10.3390/rs11010035
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Rice Cropping Intensity in Southern China from 1990 to 2015

Abstract: Assessing changes in rice cropping systems is essential for ensuring food security, greenhouse gas emissions, and sustainable water management. However, due to the insufficient availability of images with moderate to high spatial resolution, caused by frequent cloud cover and coarse temporal resolution, high-resolution maps of rice cropping systems at a large scale are relatively limited, especially in tropical and subtropical regions. This study combined the difference of Normalized Difference Vegetation Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Our study found that the multiple cropping indices were approximately 150%. Jiang et al (2018Jiang et al ( , 2019 noted that the planting area of double-cropping rice and multiple cropping indices considerably decreased in southern China, especially in the Poyang Lake plain and Hubei and Hunan plain [6,47]. They employed NLCD data to generate rice paddy masks.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the multiple cropping indices were approximately 150%. Jiang et al (2018Jiang et al ( , 2019 noted that the planting area of double-cropping rice and multiple cropping indices considerably decreased in southern China, especially in the Poyang Lake plain and Hubei and Hunan plain [6,47]. They employed NLCD data to generate rice paddy masks.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed CII is a new indicator which can be use to map cropping intensity at a finer scale compared with the existing researches [10,[12][13][14]. The modeled CII is a fractional image at the sub-pixel level, which is a kind of interval measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the existing studies have defined cropping intensity as cropping frequency (single cropping or double cropping, etc.) [4,[7][8][9][10][11][12][13][14][15] or MCI (multiple crop indexes) [16][17][18][19][20][21][22]. Cropping frequency is a hard division of crop pattern that can lead to much information loss.…”
Section: Introductionmentioning
confidence: 99%
“…Occasional, unpredicted failure to harvest due to disasters may have led to a reduced intensity in some years. Several studies have investigated the increasing and decreasing crop-intensity phenomenon [62,63]. Figure 6 shows the result obtained for the average cropping intensity of the dominant crop in the three year groups.…”
Section: Modis Cropping-intensity Productmentioning
confidence: 99%
“…The adjustment strategy can reduce errors, which could be identified by boundary analyses between Bangladesh and India, and showed a contrast difference in the boundary of the two countries, as shown in Figure 8. Further, South Asia and Southeast Asia showed high spatial variation and complexity in the sowing months as water resources were available throughout the year [62,66]. In contrast, the northern regions, such as Europe and the US, have similar climate conditions, and hence their period of cultivation is This indicates how increasing food demand in the Asia region has led to the increased development of irrigation system that have increased the number of cultivation periods in one year [64].…”
Section: Modis-amsr Sowing-month Productmentioning
confidence: 99%